Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbantuan LKPD Liveworksheets terhadap Hasil Belajar Siswa Kelas VII pada Mata Pelajaran IPA di SMP Negeri 37 Samarinda - Oktavia, Aulia Ayu; Akhmad, Akhmad; Turista, Dora Dayu Rahma; Makkadafi, Suparno Putera (Biocaster : Jurnal Kajian Biologi, 2025)
Seventh-grade students of SMP Negeri 37 Samarinda face problems in science learning, namely not achieving learning mastery. The learning process is still dominated by conventional teacher-centered methods that cause students to tend to be passive and learning media are less varied, so that learning activities are not effective. To overcome these problems, this study applies the Problem Based Learning (PBL) learning model assisted by LKPD Liveworksheets which encourages students to think critically and actively to be able to solve problems thoroughly and completely. This study aims to determine the effect of the problem based learning model assisted by LKPD Liveworksheets on the learning outcomes of seventh-grade students in science subjects at SMP Negeri 37 Samarinda. The type of research used is quantitative research with a quasi-experimental method using a non-equivalent control group design. The research sample was selected by purposive sampling consisting of classes VIIC and VIID with a total of 44 students. Data analysis was carried out using the independent sample t test and the N-Gain test. Based on the data analysis, the t-test obtained a significance value of 0.004 (p < 0.05), indicating a significant difference between the learning outcomes of students in the experimental and control classes. Furthermore, the N-Gain analysis showed that the experimental class obtained a score of 0.63, which is in the moderate category, while the control class obtained a score of 0.57, also in the moderate category. These findings indicate that the implementation of the Problem-Based Learning (PBL) model assisted by Student Worksheets (LKPD) based on liveworksheets has a positive impact on improving student learning outcomes in Natural Science (IPA) for seventh graders at SMP Negeri 37 Samarinda.